PENGARUH METODE RANGKAIAN BERMAIN DAN RANGKAIAN LATIHAN TERHADAP KETERAMPILAN BERMAIN SEPAKBOLA - Yulifri yulifri (Jurnal Sporta Saintika, 2019)
Based on the observations of researchers in the field, it can be seen that the players of Putra Ranah Minang soccer school in Padang City, their soccer playing skills are still low, and there are still many players who have not mastered basic football techniques, besides training programs that are not structured and players who are still careless in training. This type of research is a quasi experiment, the instrument used in this study is a test of football playing skills. Data were analyzed using t-test analysis. The results of data analysis showed that: (1) there were differences in the skills of playing football between groups of series of methods to play with groups of training series methods.